A 3‐D Multiuser HAP‐MIMO Channel Model Based on Dynamic Evolution of LOS Components. Issue 3 (1st May 2019) - Lian, Zhuxian; Jiang, Lingge; He, Chen; He, Di
Abstract : A theoretical Three dimensional (3D) multiuser High altitude platform (HAP) Multipleinput multiple‐output (MIMO) channel model based on dynamic evolution of the Line‐of‐sight (LOS) components is proposed. In this paper, we consider that the LOS components could re‐appear after they have vanished, and a two‐state Continuous‐time Markov chain (CTMC) is used to model the dynamic evolution of the LOS components. The survival probabilities of the LOS components are derived by using Chapman‐Kolmogorov (C‐K) equations, and the closed‐form expressions are derived in this paper. Using the survival probabilities, the spatial correlation functions are derived. Measurements show that a two‐state CTMC is indispensable to investigate the dynamic properties of the LOS components.